STRATEGI AKUN @SHELMADESS DALAM MEMBANGUN PERSONAL BRANDING DAN KARIER MELALUI PLATFORM TIKTOK - Nabilatul Leila Ihsani Putri; Umar Burhan (JMD : Jurnal Riset Manajemen & Bisnis Dewantara, 2025)
Digital transformation has encouraged Generation Z to utilize TikTok as a strategic medium to build authentic personal branding to support career opportunities. This study aims to explore how Generation Z leverages TikTok as a medium for personal branding that can support long-term career. This research uses a qualitative approach with a case study method, data collected through content observation, in-depth interviews, and documentation, and analyzed through three stages: data reduction, data presentation, and conclusion drawing, with data validity ensured through source and method triangulation. The key informant in this study was Shelma Ayu Desearsa (@Shelmadess) a content creator from Gresik who is active on TikTok with a focus on bodycare, education, and motivation content. The results showed that strategies such as niche selection, content authenticity, and visual consistency play a role in forming a strong professional image. High engagement, trend adaptation, and audience interaction also strengthen the success of personal branding. Credibility and value congruence with the brand open up opportunities for professional cooperation and support career development as a content creator. Sustainable personal branding is a strategic asset in the digital era. TikTok proves to be a potential space for Generation Z in building professional identity and expanding career opportunities.